Successful polio supplementary immunisation activities in a security compromised zone – Experiences from the Southwest region of Cameroon. Issue 46 (12th November 2018) - Haddison, Eposi C.; Ngono, Dorine; Kouamen, Gael T.; Kagina, Benjamin M.
Abstract: Background: Supplementary immunisation activities (SIAs) play a central role in polio eradication efforts. Armed conflicts resulting in insecurity negatively affect SIAs. In the Southwest region of Cameroon, armed conflicts persisted in 2018. We present our experiences of conducting a polio SIA in an insecure region. Methods: The SIA took place from the 2nd to 4th of March 2018 and targeted 307, 920 children aged 0–59 months. Bivalent polio vaccine was used. Before the SIA, extensive planning was done under the leadership of a Central Technical Group. Planning included security assessment, advocacy and social mobilisation. Results: Only 4 of the 18 health districts (HDs) of the Southwest region were considered safe. Regardless, vaccination teams worked in all HDs. The SIA achieved a coverage of 89.9%. Town criers and social mobilisers were the main sources of information about the SIA. Most (76%) children were vaccinated using the door to door strategy. There was no case of vaccine refusal. Conclusion: Community members were very receptive of the SIA and this may be due to the communication that was adopted. Strong dedication by vaccination teams, community members' understanding and acceptance of polio SIAs are all key factors to the eradication of polio in conflict zones.